(untitled) (Research, Society and Development, 2020)
The aim of this study was to identify the prevalence of acute kidney injury in Intensive Care Unit patients by isolated assessment of serum creatinine elevation and clinical application of the renal dysfunction classification Acute Kidney Injury Network. This is a prospective cohort study carried out in the Intensive Care Unit of a hospital specializing in cardiology hospital. Information was obtained from clinical and laboratory records. For the definition of acute kidney, the criteria for elevation in serum creatinine values and Acute Kidney Injury classification criteria were adopted. The final sample involved 79 patients, with a mean age of 59.8 (SD = 13.5) years. The main comorbidities were systemic arterial hypertension, congestive heart failure, diabetes mellitus and chagas disease. The prevalence of acute kidney injury was 63.3% in the evaluation of isolated serum creatinine, while, according to the Acute Kidney Injury Network criteria, 77.2% were identified. It is concluded that the Acute Kidney Injury Network criterion presents better acute kidney injury stratification than creatinine alone and can serve as an evaluation instrument in critically ill patients. As it is a method composed by usual evaluation parameters in Intensive Care Unit, it can be incorporated by the nurse in his clinical evaluation.